Efektivitas Media Interaktif Genially Menggunakan Model Problem Based Learning Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Nurhasanah, Siti; Reinita, Reinita; Putera, Rafhi Febryan; Wulandari, Fikhen Tri (Universitas Negeri Padang, 2025)
The findings that there is a dearth of creativity in technology-based learning materials are what spurred this study. Textbooks and traditional visuals are the only learning materials frequently employed in the educational process. The objective of this study is to create an interactive learning resource that is legitimate, useful, and efficient for use in the teaching and learning process. It is based on the Pancasila Education fifth-grade elementary school's Problem-Based Learning approach. Using the ADDIE development model, this study is a development study (Research and Development). Analysis, Design, Development, Implementation, and Evaluation make up the ADDIE paradigm. At UPTD SDN 010120 Ledong Timur, the trial was held. With an average score of 91.11%, the study's findings show that the created material is genuine and can be classified as